A Semana: periódico literário - MOURÃO, Sílvia Carvalho (2006)
In Brazil the coming of the Real Family in 1808, brought great changes and among them was the first periodical manifestation O Correio Brasiliense, edited in London, considered for researchers a magazine to judge for the etimologia of the appositive Armazén. From 1833 it had editions of magazines published in Brazil, Paris and New York. The beginning of XX century, over all, with the Week of Modern Art in 1922, appears magazines that break with the traditionalism as: Klaxon, Estética, Festa e others. From then onwards others had appeared that constituted important documents of the Brazilian society and registered the new trends of public reader. Pará was not absent of these events and had the Press as its main vehicle of divulgation. Some magazines and some news papers had appeared at this time in the capital of the State, among which the magazine A Semana was outstanding, that circulated for twenty five years. This weekly kept correspondence with other regions of Brazil: São Paulo, Rio de Janeiro, Recife, Maranhão. In these regions it had collaborators of the magazine, that allowed the exchange of information of what happened in the literary world and the cultural world. Of the complied periodical they had selected four (04) exemplary ones of the year of 1939 to be studied, in this work. In them had made surveys of the cover, of literary publications, the sort the one that these productions belonged and of its respective authors. For the done summary of these editions, one could perceive that the publishers looked for a pattern: they practically divulged texts of literary matrix, like stories, poems, part of romances, essays. Some of these productions had been evident that nor all had absorbed the new aesthetic trend that came with the Semana de Arte Moderna, (week of modern art) because there where writers who had oscillated between aesthetic Romantic one, Simbolista and Parnasiana. On the other hand those who had been outstanding, incorporating this new literary time. In the middle of these productions had appeared the feminine figure, in a prominence place, that beyond illustrating the cover of the periodical still appeared in the following pages. All those informations divulged in the periodical had given more credibility to the Magazine and allowed that Paraense Literature become part of this new moment of Brazilian Literature.